The Association Between Leucine and Diabetic Nephropathy in Different Gender: A Cross-Sectional Study in Chinese Patients With Type 2 Diabetes - Gao, Xiaoqian; Hou, Ruiqin; Li, Xin; Qiu, Xing-Hua; Luo, Hui-Huan; Liu, Sheng-Lin; Fang, Zhong-Ze (Frontiers in Endocrinology, 2021)
Objective This study aimed to evaluate how leucine are associated with diabetic nephropathy (DN) in type 2 diabetes (T2D) patients and the gender difference of this association. Methods We retrieved 1,031 consecutive patients with T2D who meet the inclusion and exclusion criteria from the same tertiary care center and extracted clinical information from electronic medical record. Plasma leucine was measured by liquid chromatography-mass spectrometer. Restricted cubic spline (RCS) was conducted to examine potential non-linear relationship between leucine and the risk of DN. Logistic regression was used to obtain odds ratio (OR) and confidence interval (CI). Additive interaction was used to estimate the interaction effect between leucine and gender for DN. Results We found there was a negative correlation between leucine and the risk of DN. After stratifying all patients by gender, this relationship only remained significant in women (OR:0.57, CI:0.41–0.79). Conclusions In conclusion, T2D patients with high levels of leucine have a lower risk of developing DN in female.